Glucagon: The renewal of an old hormone in the pathophysiology of diabetes (胰升糖素：一种老激素在糖尿病病理生理中的新作用). (26th April 2013) - Gosmain, Yvan; Masson, Mounia Heddad; Philippe, Jacques
Abstract Type 2 diabetes (T2D) is one of the most common diseases, affecting 5–10% of the population in most countries; the progression of its prevalence has been constant over the past 50 years in all countries worldwide, creating a major public health problem in terms of disease management and financial burden. Although the pathophysiology of T2D has been attributed for decades to insulin resistance and decreased insulin secretion, particularly in response to glucose, the contributing role of glucagon in hyperglycemia has been highlighted since the early 1970s by demonstrating its glycogenolytic, gluconeogenic and ketogenic properties. More recently, the importance of glucagon in diabetes has been highlighted in a model of streptozotocin‐induced diabetic mice becoming euglycemic in the absence of glucagon receptors and without insulin treatment. Understanding the dysregulation of α‐cells in diabetes will be critical to better define the pathophysiology of diabetes and develop new antidiabetic treatment.